1992
DOI: 10.1111/j.1365-2133.1992.tb11815.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravital video-capillaroscopy for the study of the microcirculation in psoriasis

Abstract: Intravital capillaroscopy using a video-microscopy system permits real-time imaging of the skin microvasculature with retrospective analysis of capillary dynamics. The addition of fluorescein angiography improves contrast and detects aspects of blood vessel behaviour, such as perfusion homogeneity and transcapillary solute diffusion, not detectable under native conditions. This study was performed to evaluate whether the method can be applied to the investigation of a skin disease and in particular the underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 16 publications
4
52
0
Order By: Relevance
“…Our preliminary observations confirm, in the lesional skin, the presence of many uniformly arranged tortuous and dilated loops, according to previous capillaroscopic studies [5, 15], but, in addition, we found a different pattern of distribution and morphology of capillary loops in perilesional skin. Moreover, we found an increase in capillary density in perilesional skin.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our preliminary observations confirm, in the lesional skin, the presence of many uniformly arranged tortuous and dilated loops, according to previous capillaroscopic studies [5, 15], but, in addition, we found a different pattern of distribution and morphology of capillary loops in perilesional skin. Moreover, we found an increase in capillary density in perilesional skin.…”
Section: Discussionsupporting
confidence: 79%
“…Bacharach-Bules et al [4]consider that elongation of intrapapillary capillaries is not due to angiogenesis; similarly, Bull et al [5]found that the density of capillaries was not increased in the plaque compared to the uninvolved psoriatic skin (at least 2 cm from the edge of a plaque), suggesting expansion of existing vessels and no new vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversies exist whether the initiating events are primarily epidermal or vascular [1, 10, 12, 14, 15, 16, 17, 18, 19]. The relationship if any between the extent in these two tissue hyperplasias has not been thoroughly studied so far using fractal geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship if any between the extent in these two tissue hyperplasias has not been thoroughly studied so far using fractal geometry. The classical analytical methods used to quantify these changes are based on Euclidean geometry [8, 13, 14, 15, 16, 17, 18, 19]. In some instances, fractal geometry is better suited for assessing structures with irregular shapes because quantitative data in the volume, area and length of such objects vary dramatically as a function of the scale of measurement used [19, 20, 21, 22, 23, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Videocapillaroscopy (VCP) uses an optical fiber probe connected to a microvideotelecamera, and allows morphologic and functional analysis of microcirculation at all cutaneous sites. VCP has been used for analyzing cutaneous microcirculation in skin diseases such as erythematotelangiectatic rosacea [3] and psoriasis [4, 5]. Psoriasis is a chronic inflammatory disease that involves cutaneous vessels, with the presence of elongated and dilated capillaries in the papillary dermis [6,7,8].…”
Section: Introductionmentioning
confidence: 99%